Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Find the value of the expression [tex][tex]$3m^2 + 2p^2 - 15$[/tex][/tex] when [tex][tex]$m=3$[/tex][/tex] and [tex][tex]$p=10$[/tex][/tex].

A. 27
B. 200
C. 212
D. 225


Sagot :

Certainly! Let's find the value of the expression [tex]\(3m^2 + 2p^2 - 15\)[/tex] given [tex]\(m = 3\)[/tex] and [tex]\(p = 10\)[/tex].

### Step-by-Step Solution

1. Substitute the values of [tex]\(m\)[/tex] and [tex]\(p\)[/tex] into the expression:
The given expression is:
[tex]\[ 3m^2 + 2p^2 - 15 \][/tex]
We are given [tex]\(m = 3\)[/tex] and [tex]\(p = 10\)[/tex].

2. Calculate [tex]\(3m^2\)[/tex]:
[tex]\[ m = 3 \Rightarrow 3m^2 = 3 \times (3)^2 = 3 \times 9 = 27 \][/tex]

3. Calculate [tex]\(2p^2\)[/tex]:
[tex]\[ p = 10 \Rightarrow 2p^2 = 2 \times (10)^2 = 2 \times 100 = 200 \][/tex]

4. Add the values of [tex]\(3m^2\)[/tex] and [tex]\(2p^2\)[/tex]:
[tex]\[ 3m^2 + 2p^2 = 27 + 200 = 227 \][/tex]

5. Subtract 15 from the sum:
[tex]\[ 3m^2 + 2p^2 - 15 = 227 - 15 = 212 \][/tex]

### Final Answer
Thus, the value of the expression [tex]\(3m^2 + 2p^2 - 15\)[/tex] when [tex]\(m = 3\)[/tex] and [tex]\(p = 10\)[/tex] is:
[tex]\[ \boxed{212} \][/tex]

Here are the intermediate calculations:
- [tex]\(3m^2 = 27\)[/tex]
- [tex]\(2p^2 = 200\)[/tex]
- [tex]\(3m^2 + 2p^2 - 15 = 212\)[/tex]

So, the final value of the expression is [tex]\(212\)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.